MEMPERSOALKAN PROGRAM JALUR TAMAT BELAJAR TANPA SKRIPSI Pada Program Studi Ilmu Komunikasi (sebuah penelitian awal melalui studi komparatif) - Kustiatno, Kustiatno (Universitas Prof. Dr. Moestopo (Beragama), 2006)
Communication science Faculty of University of Prof. DR. Moestopo ( Beragama ) Jakarta Always commit itself to supper the government to FulfHI one of the Indonesia Republic goal on to mate Indonesia people smarter which is written on vision and mission at the communication science of University of Prof. Dr. Moestopo (Beragama) Jakarta That is to increase the Tri Dharma activity, those are to evaluate, to maintain and to supply ideas on developing the Communication Science through teaching, researching, and devotion to the society to create strong and Independent passed graduate. Furthermore, after Communication science Faculty of University of Prof Dr. Moestopo ( Beragama ) Jakarta got A grade according to the decision of national college Accreditation Institution number 012/BAN- PT/AK-VII/S1Nll/2003 on July 2003 Hence the quality of passed graduate got serious attention from the head (dean) of Communication Science faculty and also from the University. On the other hand the quality of the passed graduate, experience shows that the percentageof the amount of passed graduate in has degradation.